Analisis Sistem Pengelolaan Rekam Medis Pendukung Klaim Jaminan Kesehatan Nasional Pelayanan Rawat Inap Di Rumah Sakit S Kota Semarang - Amir Saputro; Chriswardani Suryawati; Farid Agushybana (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2020)
Preliminary study in Hospital S showed that incomplete medical records still found and caused late claims. Based on these findings, this study analysed the medical record management system to support the National Health Insurance claim of inpatients at S Hospital.This was qualitative study using cross-sectional approach. The key informants are Hospital Director, Doctors, Coding Staffs, Casemix Staffs, Case Manager, and Internal Verificators. Whereas, the triangulation informants included Owner, Internal Auditor Unit, and Medical Committee. The data collection was done through in-depth interview and observation. Results showed that the number of human resources was enough, but the socialization about medical records to doctors was still impaired. The funding was sufficient while the infrastructure and facilities were not advanced to support the claim verification. Medical records were available and easy to fill in. Guidelines and Standard Operating Procedures were available, but doctors’ compliance with medical records was lacking. The management of medical record in supporting the claims was not well-implemented because the doctors do not have time to fill the medical resume and surgery report. The claim auditors have regularly controlled, inspected, and followed up the medical records.It is recommended that doctors should be given intense socialization about medical records and instructed to communicate with each other to fill in the medical records on time. The hospital is also recommend to do utilization review on the completeness of medical records to support the National Health and give repressive punishment to doctors who do not fill the medical records.